2013
DOI: 10.1371/journal.pone.0058360
|View full text |Cite
|
Sign up to set email alerts
|

NIKEI: A New Inexpensive and Non-Invasive Scoring System to Exclude Advanced Fibrosis in Patients with NAFLD

Abstract: AimsTo develop, validate and compare a non-invasive fibrosis scoring system for non-alcoholic fatty liver disease (NAFLD) derived from routinely obtained clinical and biochemical parameters.Methods267 consecutive patients with biopsy proven fatty liver or non-alcoholic steatohepatitis were randomly assigned to the estimation (2/3) or validation (1/3) group to develop a model for the prediction of advanced fibrosis. Univariate statistics were performed to compare patients with and without advanced fibrosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 36 publications
0
44
0
2
Order By: Relevance
“…Our results are in accordance with those of Boursier et al [24], who showed moderate diagnostic performance for BARD (AUROC 0.70). NIKEI is a newly developed NAFLD specific fibrosis score [9]. In its original publication, a very high diagnostic accuracy was reported with an AUROC of 0.97 and an NPV of 0.99.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in accordance with those of Boursier et al [24], who showed moderate diagnostic performance for BARD (AUROC 0.70). NIKEI is a newly developed NAFLD specific fibrosis score [9]. In its original publication, a very high diagnostic accuracy was reported with an AUROC of 0.97 and an NPV of 0.99.…”
Section: Discussionmentioning
confidence: 99%
“…Several algorithms including a combination of indirect markers have been developed in NAFLD patients (BARD [8], NIKEI [9], NAFLD fibrosis score [10], NASH-CRN regression score [11]) as well as in patients with chronic hepatitis C virus (HCV) infection (GUCI [12], APRI [13], FIB-4 [14], King´s score [15], Forns score [16], Lok index [17]) (S1 Table). It is unclear whether the algorithms that were developed in NAFLD patients provide a better diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Age, platelet count and/or INR are also included in several other predictive models which have not yet been validated in adult patients with NAFLD. These scoring panels incorporate a number of components known to independently predict fibrosis severity in NAFLD, including bilirubin [123] , GGT [124] and albumin [106] .…”
Section: Markers Of Impaired Hepatic Functioningmentioning
confidence: 99%
“…Using a combination of these indicators can greatly improve the diagnosis of NAFLD. Thus, according to data of Indian researchers, [36] it was found the presence of strong positive correlation between the platelet count, gamma-glutamyltranspeptidase and apolipoprotein A and the absence of liver fibrosis in patients with NAFLD (negative predictive value -94.3 %). The results of study Sakugawa and coauthors, showed that level of hyaluronic acid can be used to reliably distinguish the initial (F0-2) and severe fibrosis (F3-4) (AUC = 0.97) [37].…”
Section: Discussionmentioning
confidence: 93%